2005
DOI: 10.2320/matertrans.46.1154
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Deformation Simulation of Regularly Cell-Structured Materials with Various Column Connectivity

Abstract: A finite element method is developed to understand the in-plane, quasi-static compressive deformation mechanism and to predict elastoplastic stress-strain responses of regularly cell-structured honeycombs. Temporal evolution of geometric configuration is also observed in series in order to understand its deformed pattern. Elasto-plastic model predicts quantitatively the compression behavior of copper cell-structured materials. Fairly good agreement with experimental results assures the validity of the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Experimental studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] conducted on printed structures allow for the determination of their specific, and often individual, parameters. Based on the tests, the characteristic mechanical properties of the designed structures, such as fatigue strength [ 31 , 32 ], yield point [ 33 ] and critical force [ 34 ], are determined.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] conducted on printed structures allow for the determination of their specific, and often individual, parameters. Based on the tests, the characteristic mechanical properties of the designed structures, such as fatigue strength [ 31 , 32 ], yield point [ 33 ] and critical force [ 34 ], are determined.…”
Section: Introductionmentioning
confidence: 99%
“…A topic that has received particular attention is designing and synthesizing materials that maximize stiffness for a given density (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). A recent result demonstrated that it is possible to approach the Hashin-Shtrikhman bounds with a single-scale architected material (7), although hierarchical structures were known earlier (21).…”
mentioning
confidence: 99%